Littératie numérique et Web social en contexte associatif - Edna Castello (Centre National d'Enseignement à Distance, 2020)
The aim of this feedback is to present a digital literacy program which has been running since November 2017 until April 2018 in a Parisian organization that welcomes adult Chinese immigrants with poor communication in French. In this context, we wanted to take advantage of the keen interest these tools arouse in this type of audience to encourage communication in a French-speaking environment online, by adding reading and writing tasks on social web sites to the original program. We present the summary of these blended courses in an organizational context where learners experienced for the first time a communicative and action-oriented approach and the aim of acquiring linguistic and digital autonomy.